Creatinine Alters the Gut Microbiome in a Mouse Model of Multiple Sclerosis - Kristen M. Drescher; Hannah Pflum; Brian T. Nguyen; Jennifer M. Auchtung; Thomas A. Auchtung (Journal of the International Society of Sports Nutrition)
Background Previous studies from our laboratory have demonstrated that both creatine and its breakdown product, creatinine have anti-inflammatory properties in vitro. Both reduce the expression of toll-like receptors on the surface of mouse cells, as well as decrease the production of the proinflammatory mediator, TNF-alpha. Creatine and creatinine decrease the movement of NFkb into the nucleus. The goal of these studies is to determine whether these findings hold true in vivo. Intracerebral (i.c.) injection of Theiler’s murine encephalomyelitis virus (TMEV) induces demyelination in susceptible strains of mice and serves as a model for multiple sclerosis (MS). In these studies, we hypothesized that creatinine (CRN), a breakdown product of creatine, would reduce inflammation, a driver of demyelination, in the TMEV model as well as in MS.Methods FVB/nJ mice were i.c. inoculated with TMEV and mice were divided into two groups – controls received water containing sucrose and one group received water with CRN and sucrose. Mice were sacrificed at days 7 and 35 post-infection and brains and spinal cords examined. Feces were collected and Illumina 16S Ribosomal RNA sequencing performed to determine if there were changes in the gut microbiome.Results At 7 days, control mice had extensive inflammation in their brains compared to CRN-treated mice. By day 35, reduced levels of CD3+ T cells were observed in the spinal cords of CRN-treated mice. Feces collected at day 35 demonstrated an increase in Proteobacteria, with is involved in barrier dysfunction, while CRN-treated animals had increased levels of Actinobacteria, a mediator of barrier integrity. In addition, there was an increase in the levels of butyrate-producing bacteria, which are generally considered anti-inflammatory in the CRN-treated mice.Conclusions We conclude that CRN treatment reduces the levels of bacteria that negatively impact gut permeability thereby resulting in less inflammation and pathology in the central nervous system.